Notices of the Oriental Coins in the Society's Collections (Proceedings of the Society of Antiquaries of Scotland, 1854)
The Society's Assistant Curator provides a detailed list of the Middle Eastern, North African, Spanish and Asian coins in the Society's collections at this time. His article includes the material that each coin is made of, its place of origin and any identified rulers depicted on the coin.